Investigation of MHD Eyring–Powell fluid flow over a rotating disk under effect of homogeneous–heterogeneous reactions. (March 2019) - Gholinia, M.; Hosseinzadeh, Kh.; Mehrzadi, H.; Ganji, D.D.; Ranjbar, A.A.
Abstract: In this research, the characteristic of the Eyring–Powell Nano fluid flow due to rotating dick with various physical impacts, such as slip flow, magnetic field along with homogeneous–heterogeneous reactions is analyzed. Higher order non-linear expressions are converted to ordinary first-order differential equations and then solved using the numerical Method (4th–5th-order Runge–Kutta–Fehlberg) in Maple-18 software. The main view of this article is to investigate the impact of parameters and numbers in the problem on velocity, temperature and concentration profiles. Conclusions indicate that: the temperature profile has shown a dual behavior in terms of changes Nt and pr. T (ζ) is increased with increasing thermophoresis parameter (Nt) and is decreased with increasing Prandtl number (Pr).